A STUDY OF ACADEMIC ACHIEVEMENT AND THE ABILITY TO THINK CRITICALLY SOCIAL STUDIES, RELIGION AND CULTURE LEARNING GROUP IN ECONOMICS OF GRADE 5 STUDENTS WITH BRAIN - BASED LEARNING MANAGEMENT - Kongnun, Atitaya; Koedsuwan, Suphot; Boonkusol , Thongpan; Maharkan, Pattarapon (Academic Journal of Thailand National Sports University, 2023)
economics brain - based learning management. 2) to study the ability to think critically in brain - based learning management. 3) to study academic learning ability of critical thinking of 70 percent of the sample. There are 29 students in grade 5 in the first semester of 2021, which are randomized from random cluster sampling in the classroom of this student group at Wat Chan Samosorn School in Education Bureau, Dusit, Bangkok. Measuring tools in the research include 1) academic learning plan using brain - based learning management. 2) academic learning achievement test. 3) critical thinking test. The experiment was conducted in a single sample group, pretest, and posttest learning, analyzing the data with averaging, standard deviation, standard statistics and t - test dependent. Result 1) student’s academic learning achievement which is managed to learn by using the brain principally higher than pretest significantly at 0.05. 2) Critical thinking ability of students who are managed by using the brain principally higher than standard at 70 percent.